Performance Analysis Of Cilembu Sweet Burning Using Oven Fuel Based Liquified Petroleum Gas (LPG) - Ahmad Thoriq; Asri Widyasanti (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2019)
Cilembu sweet potato are a commodity typical of West Java's Sumedang district which will produce tasty, sweet, legit flavors and honey when burning using an oven. The conversion program of fuel oil to gas indirectly encourages modification of the cilembu sweet potato oven. The aim of this research is to test the performance of gas-fired ovens and observe the characteristics of cilembu during burning. Cilembu sweet potato burning in this study are cilembu sweet potatoes which have been stored for more than ten days, with grade B sizes (100-200 grams / tuber) and grade C (<100 grams per tuber) (SNI Number 01-4493-1998) . The burning performance parameters analyzed included the yield and weight of burned Cilembu sweet potatoes, energy to heat and increase the temperature of the material, energy to vaporize water, energy requirements for cilembu sweet potato burning process, LPG combustion energy, grill efficiency and specific energy consumption. The results showed that the burning process of 10.5 kg cilembu sweet potatoes using an oven with a temperature of 39 0C to 176 0C took 1.22 hours. The average decrease in water content during the burning process is 0.566% bb per minute for grade C and 0.368% bb per minute for grade B with the yield of burned cilembu sweet potato produced at 77.38%. Energy requirements for the cilembu sweet potato burning process were 9,410.68 KJ, LPG combustion energy was 177,050.78 KJ, burning efficiency was 5.32% and Specific Energy Consumption was 44.034,82 KJ / Kg of water vapor.